Pengaruh Corporate Governance dan Karakteristik Perusahaan Terhadap Pengungkapan Sustainability Report pada Perusahaan Transportasi di Indonesia - Muhammad Rayza Rahman; Murni Dahlena Nasution (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of corporate governance and company characteristics on transportation companies in Indonesia. The population in this study were 43 transportation companies listed on the Indonesia Stock Exchange, and the research sample consisted of 30 units of analysis using purposive sampling technique. The data analysis technique used is the classical assumption test, multiple linear regression test, the coefficient of determination test, and hypothesis testing. The results showed that corporate governance as proxied by the independent board of commissioners and the audit committee is known that the independent board of commissioners has a negative and insignificant effect on . The audit committee has a negative and insignificant effect on . The characteristics of the company as proxied by profitability (ROA) and company size are known that ROA has a negative and insignificant effect on . The size of the company has a negative and insignificant effect on the sustainability report. Then, simultaneously independent board of commissioners, audit committee, ROA, and firm size have a positive and significant effect on.